Improving Teachers for Public Examination Administration in Nigeria for 2020 Challenges - Obagah, M. O. N. (Richtmann Publishing, 2012)
The improvement of the teachers for public examination administration, sees the teachers as the insiderand fulcrum around, which the pendulum of teaching, learning and examination revolves. The myriad ofproblems besetting the conduct of the public examination can greatly be reduced when the (loce-inparenti) of the examination is adequately prepared to solve the institutionally grown problems of publicexamination. The malpractices that pervade the conducts: the endemic problems of funding, shortage ofstaff, large enrolments in examination, poor instructional facilities, and many more notwithstanding, theteacher when sufficiently endowed and empowered can surmount the gargantuan and hydra-headedproblems of public examination administration as we approach the 2020 vision challenges. Some solutionsas a way forward were proffered in this study.